Instrumento para guiar o histórico de enfermagem voltado ao atendimento de usuários que convivem com diabetes mellitus - Lindenmeyer, Cláudia Helena (Universidade do Vale do Rio dos Sinos, 2022)
Diabetes Mellitus (DM) is considered one of the biggest public health problems of our century. It is one of the most prevalent non-communicable chronic diseases worldwide and with increasing mortality rates. In this sense, the Nurse's Consultation as a private activity of the nurse can be considered fundamental in identifying health problems, in carrying out an early diagnosis and in planning care, in health interventions and in the evaluation of the resolution of each patient's treatment. Through this practice, the professional nurse can also carry out prevention, promotion and health education actions from the perspective of comprehensive care. The objective was to build an instrument to guide the completion of the Nursing History aimed at the care of users living with Diabetes Mellitus in Primary Health Care (PHC) in the city of São Leopoldo/RS. A methodological research was proposed that includes three stages. In the first stage: a) description of the health network in the municipality of São Leopoldo; b) cross-sectional study, linked to the Research Project, approved by CNPq edict 27/20 and coordinated by the Graduate Program of the Professional Master's Degree in Nursing, at the University of Vale do Rio dos Sinos – UNISINOS; c) focus group with Primary Health Care nurses; and d) documentary research. Second stage: construction of an instrument to guide the elaboration of the Nursing History aimed at users who live with Diabetes Mellitus. Third step: validation of the instrument. It was found that the network in São Leopoldo has a coverage of 41.62% of the population. In this network, 4,601 medical records of users who live with chronic diseases, such as Hypertension, Diabetes Mellitus and obesity, were researched. Of these, 36.2% were diagnosed with Diabetes Mellitus. A focus group was carried out with six nurses from the Primary Health Care network in the municipality and, after analyzing the speeches, two categories were identified: strengths in the assistance to users who live with Diabetes Mellitus and challenges in the assistance to users who live with Diabetes Mellitus , plus five subcategories. From the results of the first stage, the product of the study was elaborated and validated: an instrument to guide the elaboration of the Nursing History aimed at the care of users who live with Diabetes Mellitus, promoting the implementation of the Nursing Process. It was discussed that care for users with Diabetes Mellitus represents a major challenge for health professionals, especially for nurses. In this sense, the construction and validation of the instrument to guide the Nursing History will be able to qualify the care for this user, focusing on improving adherence to treatment, preventing the exacerbation of the disease and reducing and preventing sequelae, which may also result in the improve the quality of life of this population. The product of this research, an instrument to guide the Nursing History, will be able to qualify the Nurse's consultation in the perspective of enabling the recording of the necessary aspects to be addressed in the consultation, as well as planning the actions of professionals in the care of the user with Diabetes Mellitus in the Attention Primary to Health.
Keywords: Diabetes mellitus; Processo de enfermagem; Atenção primária à saúde; Enfermeiro histórico de enfermagem; Nursing process; Primary health care; Nursing history nurse; ACCNPQ::Ciências da Saúde::Enfermagem